Effects of Radiation on Magnetohydrodynamic Convection Flow past an Impulsively Started Vertical Plate Submersed in a Porous Medium with Suction - Dahake, SP; Dubewar, AV (International Journal of Computer Sciences and Engineering, 2025)
The thermal effects of the suction velocity, in conjunction with other flow parameters, on an unsteady free convective viscous incompressible flow past an infinite vertical flat plate submersed in a saturated porous medium is investigated. The effect of various flow parameters like chemical reaction parameter Kr, Schimdt number Sc, radiation absorption coefficient Q1, heat absorption coefficient φ radiation parameter N, Magnetic parameter M, Permeability parameter K, and time t on the velocity, temperature and concentration as well as the skin friction, rates of heat and mass transfer are obtained numerically and discussed. The results obtained are presented with the help of graphs.